Work-home interaction and psychological distress during the COVID-19 pandemic: The mediation effect of cyberloafing - Sari Novianti; Bertina Sjabadhyni (HUMANITAS: Indonesian Psychological Journal, 2021)
Work from home is one of the policies chosen by the government due to the COVID -19 pandemic; however, work-home interactions (WHIs) can place a burden on one domain. This study aimed to examine the relationship between the dimensions of WHIs and psychological distress and how cyberloafing mediates this relationship. Data were collected with an online survey tool from 2,349 participants who worked at a government institution in Indonesia with employees across the country to test the proposed hypothesis. The results show that all forms of WHIs cause psychological distress. Further, a high level of negative work-home interactions (NWHIs) and negative home-work interactions (NHWIs) increase psychological distress. Conversely, a high level of positive work-home interactions (PWHIs) and positive home-work interactions (PHWIs) reduce psychological distress. In addition, this studys results also show that cyberloafing mediates the relationships between NWHIs, NHWIs, PWHIs, and psychological distress. This study implies the organization need to provide mental support and technology support to ensure the work of employees effective. Organizations also need to support employees to reduce work-family conflict.